Video: Mainan Dan Bermain - Wati, Wahyu Utami (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2013)
Â Playing is an expression of human's attempt to make him happy and comfortable. Playhas a broad meaning, but in the process of creating this work of understanding playingis more focused on the activities by the children who use the instrument of playing, ietoys.Toy is re-representated into a videography work that is presented in a video installationforms. To be able to play the video required a response from the audience. Responserequired is pressure on the plate that had been given Force Sensitive Resistor. Thepressure will be captured and linked to the four channel video which will then play thevideo.The purpose of creating the work "Video: Toys and Play" is to explore the toys in theform of video work. This video is presented in the form of interactive work. Interactive isone of the elements of the play. The presentation with interactive techniques is chosento make the audience as an active audience and be part of the videography work.